(NnUKLONNYE ASSOCIACII W ATOMNYH QDRAH I QDERNYE REAKCII MNOGONUKLONNYH PEREDA^ (B/s - (NnEMEC(B, (NoLEG fEDOROWI^s; (NnEUDA^IN(B, (Nw(B.(Ng(B.s; (NrUD^IK(B, (Na(B.(Nt(B.s; (NfILIPPOW(B, (NgENNADIJ fEDOROWI^s; (NuKRAINSKIJ IN(B-(NT QDERNYH ISSLEDOWANIJs ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 466-488 (536 (NNAZW(B.)s
Keywords: (NnUKLONY s